A checklist of ciliate parasites (Ciliophora) of fishes from Mexico - Aguilar-Aguilar, Rogelio; Islas-Ortega, Alma Gabriela (Zootaxa, 2015)
A database with all available published accounts of the ciliate parasite species of Mexican fishes was assembled. This information, along with records derived from own recent research, allow generating a checklist containing all the records, which is a necessary first step to address future questions in the areas of ecology, evolutionary biology and biogeography of these host-parasite associations. The checklist is presented as a parasite-host list, and a host-parasite list. The checklist contains 30 nominal species, from 9 genera and 8 families of ciliate parasites. Most of the primary records were done for exotic fish species, artificially introduced to Mexico for aquaculture purposes; however, recent works have been conducted in diverse species of native fishes. Excepting one, all the ciliate species listed here have been previously recorded for diverse fish species from different localities around the world. Based on the amount of information contained in this checklist, much more effort is necessary to accurately know the diversity of species of this type of parasites in fish fauna of Mexico.